Coin Counting Device Kinematic Diagram Development (Journal of Universal Science Research, 2024)
Coin counting machines not only speed up the coin counting process, but also increase the accuracy and efficiency of cash handling, which is a key factor for businesses and organizations that handle cash. In this article, the authors consider the requirements that must be taken into account when developing coin counting machines. The main components of a coin counter are also discussed. Development of a kinetic scheme of a coin feeder.